The rise of money to the skies: The structural limits of capital appreciation, casino capitalism and the global financial crisis - Kurz, Robert (Geografares, 2019)
This article was first published in the German magazine KRISIS: Kritik der Warengesellshaft, volumes 16 and 17, in 1995. The Portuguese version was published in May 2002, on the website <www.obeco.planetaclix.pt> and was translated from the original on the website of the German magazine Exit!, accessible at <http:// www.exit-online.org/link.php?tabelle=autoren&posnr=83>. For this Brazilian version we used the Portuguese translation. The bibliographic references used by the author in the text, with translation and publication in Brazil, have been updated. Terms that may have been modified will be indicated in a note, with the acronym N.T. (translator’s note). We are very grateful for the authorization for this revision of the translation granted by Roswitha Scholz and by Boaventura Antunes, member of Coletivo Obeco and initial translator.